PROBLEMATIC AND CURRENT KNOWLEDGE OF THE TIERRA BLANCA JOVEN TEPHRAS IN THE METROPOLITAN AREA OF SAN SALVADOR, EL SALVADOR - Chávez, José A. (2011)
Currently the Metropolitan Area of San Salvador (AMSS) is experimenting serious problems of massmovements, erosion, collapse or settlements, phenomena that in El Salvador are popularly encompassed by the term“carcavas”. This problematic is presented mainly in the volcanic tephras Tierra Blanca Joven (TBJ), product of thelast plinian eruption of Ilopango Caldera, whose products are an intercalation of pyroclastic fall, flows and surge. Thetephras are unsaturated and the geotechnical information shows a decrease of shear strength and collapse when satu-rated. To characterize properly this material is important to know the relationship of moisture content with the volumechanges and apparent cohesion, which are related to suction and cementation. The understanding of the behavior of thegeological materials can help in running slope stability simulations and geotechnical design in general.